Effects of Robots Development on Employees Perception of Human-Robots Collaboration in Hospitality Industry - Parvez, Muhammad Omar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
Robotics technology has transformed the work environment toward automation and affects employees’ assessment of robots. Therefore, this dissertation aims to examine whether the introduction of robots influences employees’ behavioral intentions to use robots and awareness of robots to promote human-robot collaboration (HRC). Besides, the role of strategic human resource management (HRM) involvement as a moderator in the perception of robots as a team member was investigated. This thesis followed a quantitative method to examine employees’ behavioral intentions to use robots and awareness of robots in promoting human-robot collaboration (HRC), and 500 data were collected from hospitality employees via the Amazon Mechanical Turk platform in the USA. After data cleaning, 329 valid responses were analyzed. Partial least squares structural equation modeling was applied using Smart PLS Ver. 3.0 to test the study’s measurement and proposed research model. The dissertation results show that robots’ perceived usefulness and ease of use positively increase employees’ behavioral intentions to use robots. In addition, the advantages and disadvantages of robots have a positive impact on robot awareness. Employees’ behavioral intentions and awareness contribute positively to human robot collaboration. On the other hand, the moderating role of strategic HR’s involvement in the relationships was insignificant. Based on the literature review, to the best of the authors’ knowledge, this study is one of the first on this topic. It extends TAM with new antecedents related to robot use, robot awareness, and HRC in the travel, tourism, and hospitality (TTH) industry. In addition, this model attempts to determine the factors that favor HRC in the industry. The study results reveal important implications for strengthening human robot cooperation in the tourism and hospitality industry. Keywords: Service Robot, Robot Adoption, Robot Awareness, Human-Robot Collaboration, Strategic HRM, Hospitality Industry

ÖZ: Robot teknolojisi çalışma ortamını otomasyon bağlamında dönüştürmüş ve çalışanların robot algısını etkilemiştir. Bu tez, çalışanların robot kullanmaya yönelik davranışsal niyetlerini ve insan-robot iş birliğini teşvik etmek için robot farkındalığını etkileyip etkilemediğini incelemeyi amaçlamıştır. Ayrıca, robotların bir ekip üyesi olarak algılanmasında stratejik insan kaynakları yönetiminin (İKY) düzenleyici rolü incelenmiştir. Bu tez, çalışanların robot kullanmaya yönelik davranışsal niyetlerini ve insan-robot iş birliğini teşvik etmede robotlara yönelik farkındalığı analiz etme kapsamında nicel bir yöntem izlemiştir. Amazon Mechanical Turk platformu aracılığıyla ABD'deki ağırlama endüstrisi çalışanlarından 500 veri toplanmıştır. Veri ayıklanması işlemi sonunda, 329 geçerli anket analize dahil edilmiştir. Önerilen etkileri ve araştırma modelini test etmek için kısmi en küçük kareler yapısal eşitlik modellemesi (PLS SEM) Smart PLS Ver 3.0 kullanılarak yapılmıştır. Araştırma sonuçları, robotların algılanan kullanışlılığının ve kullanım kolaylığının, çalışanların robot kullanmaya yönelik davranışsal niyetlerini olumlu yönde etkilediğini göstermektedir. Ayrıca robotların avantaj ve dezavantajları robot farkındalığını olumlu yönde etkilemektedir. Çalışanların davranışsal niyetleri ve farkındalıkları, insan-robot iş birliğine olumlu olarak katkıda bulunmaktadır. Öte yandan, insan kaynakları yönetiminin düzenleyici rolü istatistiksel olarak anlamlı çıkmamıştır. Mevcut literatür taraması ve bulgular, bu çalışmanın bu konudaki ilk çalışmalardan biri olduğunu ve turizm endüstrisinde robot kullanımı, robot farkındalığı ve insan robot iş birliği ile ilgili yeni öncüllerle Teknoloji Kabul Modelini genişlettiğini yansıtmaktadır. Ayrıca bu model, endüstride insan-robot iş birliğini destekleyen faktörleri belirlemiştir. Çalışmanın sonuçları, turizm ve konaklama endüstrisinde insan-robot iş birliğinin güçlendirilmesi kapsamında önemli çıkarımlar ortaya koymaktadır. Anahtar Kelimeler: Hizmet Robotu, Robot Benimseme, Robot Farkındalığı, İnsan Robot İş Birliği, Stratejik İnsan Kaynakları Yönetimi, Ağırlama Endüstr
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2022. Co-Supervisor: Prof. Dr. Hüseyin Araslı and Supervisor: Prof. Dr. Ali Öztüren.
Keywords: Tourism; Robots--Hospitality Industry--Tourism; Service Robot; Robot Adoption; Robot Awareness; Human-Robot Collaboration; Strategic HRM; Hospitality Industry